Eficacia del tratamiento fisioterapéutico de las lesiones más frecuentes de la rodilla en los pacientes que asisten al hospital del seguro de la ciudad de Loja en el periodo enero-julio 2010” - Puertas Mora, Bertha Marisol (2010)
To carry out this work by examining the importance of appropriate and effective treatment for rupture of the crusade ligaments so our theme to investigate: “EFFECTIVENESS OF PHYSIOTHERAPY IN PATIENTS WITH CRUCIATE LIGAMENT PLASTY OF THE KNEE SEEN IN THE AREA OF GENERAL HOSPITAL PHYSIATRY RIOBAMBA”. During the period July 2009 to January 2010" This research work has three main parts are: Chapter one which corresponds to the reference frame in which we formulate the problem to be addressed in order to determine what the effectiveness of physiotherapy to recover the patient with ACL plasty knee.